Comparison of the Cost-Effectiveness and Safety between Staged Bilateral Total Knee Arthroplasty and Simultaneous Bilateral Total Knee Arthroplasty: A Retrospective Cohort Study between 2001 and 2022 - Tsui, Omar W.K.; Chan, Ping-Keung; Cheung, Amy; Chan, Vincent W.K.; Luk, Michelle H.; Cheung, Man-Hong; Lau, Lawrence C.M.; Leung, Thomas K.C.; Fu, Henry; Chiu, Kwong-Yuen (The Journal of Knee Surgery, 2024)
A substantial proportion of Hong Kong's aging population suffers from osteoarthritis in both knees. Bilateral total knee arthroplasty (BTKA) is a surgical option for addressing this condition and can be performed via two approaches: simultaneous BTKA (SimBTKA) and staged BTKA (StaBTKA). We compared the cost-effectiveness and safety of these two methods in our institution. We retrospectively reviewed 2,372 patients (SimBTKA, 772; StaBTKA, 1,600; females, 1,780; males, 592; mean age at SimBTKA, 70.4 ± 7.99 years; mean age at StaBTKA, 66.4 ± 7.50 years; p < 0.001) who underwent BTKA in our institution from 2001 to 2022. Patients were categorized according to the surgical approach. Patients undergoing BTKA in our institution were included. Particularly for SimBTKA, patients were assessed by anesthetists to be medically fit before undergoing the procedure according to their age, American Society of Anesthesiologists status, and osteoarthritis severity. The primary outcome was the length of stay (LOS) after surgery. The secondary outcomes were the 30-day unintended readmission, intensive care unit (ICU) admission, and death. SimBTKA had a shorter mean total LOS (acute hospital + rehabilitation center; SimBTKA, 13.09 days; StaBTKA, 18.12 days; p < 0.001) and mean LOS in acute hospital (SimBTKA, 7.70 days; StaBTKA, 10.42 days; p < 0.001). However, no significant difference was found in the mean LOS in rehabilitation centers (SimBTKA, 5.47 days; StaBTKA, 6.32 days; p > 0.05) between the two approaches. The 30-day unintended readmission rate was lower in SimBTKA (SimBTKA, 2.07%; StaBTKA, 3.30%; odds ratio [OR] = 1.60; p > 0.05) but statistically insignificant. SimBTKA was less costly than StaBTKA by US$ 8,422.22 per patient. No significant differences in ICU admission and death rates were found (p > 0.05) between the two groups. SimBTKA had a shorter LOS and lower cost than StaBTKA and comparable complication rates. Therefore, SimBTKA should be indicated in medically stable patients.
Keywords: total knee arthroplasty; cost-effectiveness; aging; pain; anesthesia